Coral reef benthic community changes in the Anthropocene Biogeographic heterogeneity, overlooked configurations, and methodology - Reverter, Miriam (Global change biology, 2022)
© 2021 The Authors. Global Change Biology published by John Wiley & Sons Ltd.